LINGUOCULTURAL FEATURES OF SPEECH FORMULAS IN THE TRANSLATIONS OF ABDULLA QODIRIY'S "MEHROBDAN CHAYON" - Raximova Iroda Baxodirovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the linguocultural features of speech formulas in the translations of Abdulla Qodiriy's "Mehrobdan chayon", a cornerstone of Uzbek literature. Speech formulas—idiomatic expressions, proverbs, metaphors, and culturally specific phrases—serve as key linguistic tools that reflect the traditions, values, and worldview of Uzbek society. The study examines how these culturally rich expressions are represented in English translations and highlights the challenges faced in preserving their original meaning and cultural significance. Using a comparative linguocultural analysis, the article identifies key speech formulas from the original Uzbek text and evaluates the strategies used to translate them, such as literal translation, paraphrasing, contextual adaptation, and explanatory additions. The findings reveal that while literal translations often fail to convey the cultural depth of the original text, adaptive strategies like paraphrasing and contextualization help maintain cultural authenticity. This research underscores the importance of linguocultural awareness in literary translation and offers practical recommendations for translators dealing with culturally specific content. It contributes to the broader field of translation studies by emphasizing the balance between linguistic accuracy and cultural fidelity, ensuring that literary works retain their original richness when presented to global audiences.